Faktor-Faktor yang Mempengaruhi Sikap Pengguna terhadap Teknologi Cashless pada Generasi Z Di Indonesia - Sanapang, Gracela Marisa; Kohar, Felicia; Nurtani, Leony Putri; Santoso, Robin Christoffel (Movere Journal, 2025)
This study aims to explore the factors that influence user attitudes towardscashless technology in Indonesia. The increasing adoption of cashless payment systemsis essential to understand the elements that shape positive user attitudes. This studyuses a quantitative approach, analyzing the influence of Perceived Usefulness,Perceived Ease of Use, Trust in Technology, and Perceived Risk on cashless userattitudes. The respondents in this study were 385 from generation Z. Data werecollected by providing a series of structured questions through a survey involvingrespondents who use cashless technology, and multiple linear regression analysis totest the proposed hypothesis. The results of the study indicate that perceived benefitsand ease of use have a significant positive impact on user attitudes, while the level oftrust and risk perception also have an effect, but with different complexities. Thesefindings provide insights for technology developers and stakeholders to design moreeffective strategies in increasing the adoption of cashless technology in society. Thisresearch is expected to contribute to the development of a more inclusive and efficientpayment ecosystem.